Komunikasi Nahdlatul Ulama dalam Pengembangan Ekonomi Umat - Didin Sutisna (Communicatus: Jurnal Ilmu komunikasi, 2018)
This paper aims to find out the communication patterns of the Nahdatul Ulama in Community Economic Development in West Java, in order to improve the welfare of the community, especially those that have received less attention from the government. In addition to strengthening the economy of the people, PWNU West Java also has a goal to foster and motivate religious life in the community as mad'u. As well as to find out the strategy of economic development which was proposed by the West Java PWNU and its implementation. The research method using the case study method with the type of research is qualitative and the Constructivism Paradigm. While the data source in the study is divided into two parts, namely primary sources and secondary data sources. The data collection method is obtained by observation, interviews, and documentation studies. The results of the study indicate that the pattern of organizational communication in the Management of the Region of Nahdatul Ulama in West Java is the Wheel Pattern. In this pattern the chairperson is a central position in which all West Java PWNU members provide information and reports to the general chairman and if there is a problem that urges the general chairman to consult directly to solve the problem by asking for advice and approval from the PWNU West Java advisory board. Regarding economic issues, the benefits of the West Java PWNU have begun. Because some economic activities are already underway. Even though it hasn't arrived at a satisfying stage, because it does require time that is not instant.Tulisan ini bertujuan untuk mengetahui pola komunikasi Nahdlatul Ulama dalam Pengembangan Ekonomi Umat di Jawa Barat, guna meningkatkan kesejahtraan masyarakat khususnya yang kurang mendapat perhatian dari pemerintah. Selain untuk memperkuat ekonomi umat, PWNU Jawa Barat juga memiliki tujuan untuk membina dan memotivasi masyarakat dalam kehidupan beragama sebagai mad’u. Serta mengetahui strategi pengembangan ekonomi yang di gagas PWNU Jawa Barat dan pelaksanaanya. Metode penelitian menggunakan metode studi kasus dengan jenis penelitian adalah kualitatif dan Paradigma Konstruktivisme. Sedangkan sumber data pada penelitian terbagi ke dalam dua bagian yakni sumber data primer dan sumber data sekunder. Adapun metode pengumpulan data diperoleh dengan cara observasi, wawancara, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa pola komunikasi organisasi di Pengurus Wilayah Nahdatul Ulama Jawa Barat adalah Pola Roda. Dalam pola ini, ketua umum menjadi posisi sentral yang dimana seluruh anggota PWNU Jawa Barat memberikan informasi dan laporan kepada ketua umum dan apabila ada masalah yang penting, maka ketua umum dapat berkonsultasi langsung untuk memecahkan masalah dengan meminta saran dan persetujuan syuriah atau dewan penasehat PWNU Jawa Barat. Berkaitan dengan persoalan perekonomian, yang telah dilakukan PWNU Jawa Barat sudah mulai terasa manfaatnya. Karena beberapa kegiatan ekonomi sudah berjalan. Walaupun memang belum sampai pada tahap memuaskan, serta memerlukan waktu untuk tercapainya target yang ditentukan.